Blood Cell Count-Based Inflammatory Markers Exhibit Superior Association with Diabetic Peripheral Neuropathy Compared to Protein-Based Markers - Ko FS; Wu TH; Su GY; Lin YH; Juan CC; Hwu CM (Journal of Inflammation Research)
Fu-Shun Ko,1 Tsung-Hui Wu,1,2 Guan-Yu Su,1,2 Yi-Hsiu Lin,3 Chi-Chang Juan,3,4 Chii-Min Hwu1,2 1Section of Endocrinology and Metabolism, Department of Medicine, Taipei Veterans General Hospital, Taipei, Taiwan; 2Faculty of Medicine, National Yang Ming Chiao Tung University College of Medicine, Taipei, Taiwan; 3Institutes of Physiology, College of Medicine, National Yang Ming Chiao Tung University, Taipei, Taiwan; 4Department of Medical Research, Taipei Veterans General Hospital, Taipei, TaiwanCorrespondence: Chii-Min Hwu, Section of Endocrinology and Metabolism, Department of Medicine, Taipei Veterans General Hospital, 201, ShiPai Road Sec. 2, Chung-Cheng Build. 11F Room 522, Taipei, 112, Taiwan, Tel +886 2 2875 7516, Fax +886 2 2875 1429, Email chhwu@vghtpe.gov.twBackground: Diabetic peripheral neuropathy (DPN) is a prevalent and disabling complication of type 2 diabetes mellitus, contributing to poor quality of life and increased healthcare burden. Chronic low-grade inflammation has been proposed as a key contributor to the pathogenesis of DPN. While various inflammatory markers have been studied, their diagnostic utility remains unclear, particularly when comparing protein-based markers and blood cell count-derived ratios.Objective: This study aimed to investigate whether blood cell count-based inflammatory markers, such as the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), are more strongly associated with DPN compared to protein-based markers, including interleukin-1 receptor antagonist (IL-1Ra) and high-sensitivity C-reactive protein (hsCRP).Methods: In this cross-sectional study, 137 patients with type 2 diabetes were recruited. DPN was defined as a Michigan Neuropathy Screening Instrument (MNSI) score ≥ 2. All participants underwent physical examinations, questionnaire assessments, and laboratory evaluation of inflammatory markers.Results: NLR was significantly elevated in the DPN group compared to controls (P < 0.05), while IL-1Ra and hsCRP levels showed no significant differences. Participants in the highest NLR tertile exhibited a higher DPN prevalence (19.0%) than those in the lowest tertile (8.8%). Multivariate linear regression identified NLR and HbA1c as independent predictors of MNSI scores.Conclusion: Our findings demonstrate that the NLR, an inflammation-related marker derived from peripheral blood cell counts, is significantly associated with DPN, whereas protein-based markers did not demonstrate clear associations. These findings suggest that NLR may serve as a simple, cost-effective biomarker for identifying patients at risk for DPN. Further longitudinal studies are warranted to clarify causal relationships and evaluate its prognostic value.Keywords: type 2 diabetes mellitus, diabetic peripheral neuropathy, inflammatory response, IL-1 receptor antagonist